Crystallographic characterization of Ag‐doping in nanocrystallite hydroxyapatite and evaluation of photocatalytic activity of organic pollutants - Md. Sahadat Hossain; Shifa Sarkar; Samina Ahmed (International Journal of Ceramic Engineering & Science)
Abstract Pure and different percentages (0.25, 0.5, 1.0, and 2.5%) of silver (Ag) doped hydroxyapatites (Hap) were synthesized employing the wet chemical precipitation method. The samples were characterized with the aid of X‐ray diffraction (phase analysis, crystallographic characterization, and crystal size calculation using Scherrer equation and different models), scanning electron microscopy, and optical bandgap energy. The Hap containing 0.25% Ag showed better photocatalytic activity in various dye concentrations, catalyst doses, and pH. At a very low catalyst dose (0.375 g/L) and 20 ppm pollutant concentration, reaction rate, and rate constant were evaluated for the Congo Red dye, ciprofloxacin, amoxicillin, and levofloxacin. The maximum rate constant (0.0028 min−1) and reaction rate (9.657 × 10−8 mole L−1·min−1) were found for Congo Red dye and ciprofloxacin, respectively, using 0.25_Ag‐Hap (0.25% Ag‐doped Hap). The energies of the valance band (3.14 eV) and conduction band (−0.36 eV) were lower in the case of 0.25_Ag‐Hap than the other samples. Simplified reaction mechanisms were proposed for the photocatalytic degradation of Congo Red dye, ciprofloxacin, amoxicillin, and levofloxacin.